Scope and dilemmas of the M. Beuchot’s analogical Ethics - Seguró, Miquel; Palazzi, Cristian (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This paper discusses the scope of the axiological proposal of M. Beuchot’s "analogical hermeneutics". The first step to do it set out the ontological foundationwhich is based its proposal. In a second moment the paper proceeds to clarificate the "translation" to the axiological field and its ethical problems. Finally, in a third step seeks to show the aporetic principles finded in his resolution of the ethical dilemmas. The ground of the problematic is none other than the inescapable finitude of the human ontological reality and its obvious influence on the foundations of the ethical issue.